Pengaruh Media Pembelajaran Quipper School terhadap Minat dan Hasil Belajar Siswa pada Mata Pelajaran PAI di SMA Negeri 1 Kinali - Ida Rosanti; Iswantir M; Afrinaldi Afrinaldi; Charles Charles (Journal on Education, 2023)
The purpose of this study was to determine the effect of Quipper School learning media on students' interest and learning outcomes in PAI subjects. The method used in this study was a Quasi Experiment with The Static Group Comparison design: Randomized Control Group Only Design by applying Quipper School learning media to an experimental class of 35 people and a control class of 36 people. Research data on student interest and learning outcomes were collected by means of questionnaires and tests, then analyzed using the Manova test with the help of SPSS version 22. The findings of this study are hypothesis testing, 1) There is an influence of Quipper School learning media on student learning interest in subjects PAI at SMAN 1 Kinali. Obtained from a significance value smaller than 0.05, namely 0.000 <0.05, which means a significant effect. The results showed that the average score of students' interest in learning in the control class was 67, while the average score of interest in learning in the experimental class was 87, which was in the very high category. 2) There is an influence of Quipper School learning media on student learning outcomes in PAI subjects at SMAN 1 Kinali. Obtained from a significance value smaller than 0.05, namely 0.000 <0.05, which means a significant effect. The results showed that the average score of student learning outcomes in the control class was 67 while the average score of interest in learning in the experimental class was 85. There was a significant difference between the control class and the experimental class. 3) There is an influence of Quipper School learning media on students' interest and learning outcomes in PAI subjects at SMAN 1 Kinali. The results showed that the value of ????ℎi????????????g = 86,904 with ???????????????????????? = 3.29 (????ℎi????????????g > ????????????????????????) Thus ????0 is rejected and accepts 1.0.